Exposure contrasts associated with a liquefied petroleum gas (LPG) intervention at potential field sites for the multi-country household air pollution intervention network (HAPIN) trial in India: results from pilot phase activities in rural Tamil Nadu - Sankar Sambandam; Krishnendu Mukhopadhyay; Saritha Sendhil; Wenlu Ye; Ajay Pillarisetti; Gurusamy Thangavel; Durairaj Natesan; Rengaraj Ramasamy; Amudha Natarajan; Vigneswari Aravindalochanan; A. Vinayagamoorthi; S. Sivavadivel; et al. (BMC, 2020)
Abstract Background The Household Air Pollution Intervention Network (HAPIN) trial aims to assess health benefits of a liquefied petroleum gas (LPG) cookfuel and stove intervention among women and children across four low- and middle-income countries (LMICs). We measured exposure contrasts for women, achievable under alternative conditions of biomass or LPG cookfuel use, at potential HAPIN field sites in India, to aid in site selection for the main trial. Methods We recruited participants from potential field sites within Villupuram and Nagapattinam districts in Tamil Nadu, India, that were identified during a feasibility assessment. We performed. (i) cross-sectional measurements on women (N = 79) using either biomass or LPG as their primary cookfuel and (ii) before-and-after measurements on pregnant women (N = 41), once at baseline while using biomass fuel and twice - at 1 and 2 months - after installation of an LPG stove and free fuel intervention. We involved participants to co-design clothing and instrument stands for personal and area sampling. We measured 24 or 48-h personal exposures and kitchen and ambient concentrations of fine particulate matter (PM2.5) using gravimetric samplers. Results In the cross-sectional analysis, median (interquartile range, IQR) kitchen PM2.5 concentrations in biomass and LPG using homes were 134 μg/m3 [IQR:71-258] and 27 μg/m3 [IQR:20-47], while corresponding personal exposures were 75 μg/m3 [IQR:55-104] and 36 μg/m3 [IQR:26-46], respectively. In before-and-after analysis, median 48-h personal exposures for pregnant women were 72 μg/m3 [IQR:49-127] at baseline and 25 μg/m3 [IQR:18-35] after the LPG intervention, with a sustained reduction of 93% in mean kitchen PM2.5 concentrations and 78% in mean personal PM2.5 exposures over the 2 month intervention period. Median ambient concentrations were 23 μg/m3 [IQR:19-27). Participant feedback was critical in designing clothing and instrument stands that ensured high compliance. Conclusions An LPG stove and fuel intervention in the candidate HAPIN trial field sites in India was deemed suitable for achieving health-relevant exposure reductions. Ambient concentrations indicated limited contributions from other sources. Study results provide critical inputs for the HAPIN trial site selection in India, while also contributing new information on HAP exposures in relation to LPG interventions and among pregnant women in LMICs. Trial registration ClinicalTrials.Gov. NCT02944682 ; Prospectively registered on October 17, 2016.